Decision Support System for the Selection of Courses in the Higher Education using the Method of Elimination Et Choix Tranduit La Realite - Made Sudarma; Anak Agung Kompiang Oka Sudana; Irwansyah Cahya (International Journal of Electrical and Computer Engineering (IJECE), 2015)
Each year thousands of prospective students attend new student enrollment in universities, which each prospective student have determined the courses that wish to be studied in college. Most of prospective student choose the courses only based on the number of enthusiasts and wishes of parents, and are not based on their academic ability. The impact of this phenomenon is that many of the prospective students chosen to switch courses and not a few of them have been punished dropout. This problem can be solved through the creation of decision support system that has an ability to suggest suitable courses to be selected by the prospective student based on their academic ability. This decision support system solved the problem using the method of elimination et choix tranduit la realite which is presented in web-based application to raise the accessibility by the prospective student.